A community-oriented workflow reuse and recommendation technique. (2015) - Zhang, Jia; Lee, Chris; Votava, Petr; Lee, Tsengdar J.; Nemani, Ramakrishna; Foster, Ian
NASA Earth Exchange (NEX) is a collaborative compute platform aiming to improve the availability of Earth science data, models, analysis tools and scientific results through a centralised environment that fosters knowledge sharing, collaboration, innovation and direct access to compute resources. One of the main objectives of NEX is to help Earth scientists leverage and reuse various data processing software modules developed by their peers, in order to quickly run value-added executable experiments (workflows). Toward this goal, this paper reports our efforts of leveraging social network analysis to intelligently extract hidden information from data processing workflows. By modelling Earth science workflow modules as social entities and their dependencies as social relationships, this research opens up new vistas for applying social science to facilitate software reuse and distributed workflow development. As a proof of concept, a prototyping system has been developed as a plug-in to the NEX workflow design and management system (VisTrails) to aid Earth scientists in discovering and reusing workflow modules and extending them to solve more complex science problems.